The CIA War in Kurdistan: The Untold Story of the Northern Front in the Iraq War - Faddis, Sam (Casemate Publishers, 2020)
Intro -- Title -- Contents -- Preface -- Dedication -- Preface -- Introduction -- 1 9/11 -- 2 The Plan -- 3 The Team -- 4 Getting In -- 5 Why Are You Here? -- 6 Khurmal -- 7 Missing the Shot -- 8 The Return -- 9 Base Life, Drills, and Plans for Escape -- 10 Recruiting Sources-Getting Tough -- 11 Hunting WMD -- 12 The Boneyard-Chem and Radiation -- 13 Management/Leadership and Base Life -- 14 The Turks and Tension-Border Closed-Supply Runs -- 15 Fishing for Assassins -- 16 One Team, One Fight -- 17 Propaganda, Transmitters, and Country Music -- 18 Chalabi and the Pentagon-Badr Corps, Marines, Supply from Space -- 19 Mutiny and Training Kurdish Teams -- 20 10th Group, Deploying Kurdish Teams, Air War and Hunting Fedayeen -- 21 The 173rd Takes Harir, Losing the Surrender -- 22 Kirkuk and Mosul -- 23 Coming Home -- 24 Lessons -- Copyright.